Genome-wide association study of Ethiopian barley germplasm reveals putative genomic loci underlying root system architectural traits at seedling stage - Babiye, B.; Negawo, Alemayehu T.; Ejerso, W.F.; Gidamo, G.H.; Alemu, S.K.; Teklemariam, S.S.; Woldesemayat, A.A. (BioMed Central, 2025)
Background: The root system architectural (RSA) trait is one of the factors that contribute to yield. In the current situation, developing new crop cultivars with efficient RSA has great potential to enhance soil resource use efficiency and improve crop production and productivity. The aim of this study was to determine the SNP markers associated with the development of RSA traits in natural growing conditions without biotic and abiotic stress conditions at the seedling stage. In this study we evaluated the natural variation of RSA traits of 260 diverse Ethiopian barley germplasm and used to identify genomic regions associated with root traits. The genotypes were grown for 21 days in plastic pots and phenotyped for 11 RSA traits. The barley genotypes were genotyped using the barley 50kiSelect SNP arrays and genome-wide association study was performed using the FarmCPU model to detect genotype phenotype associations.